2020
DOI: 10.3390/universe6110197
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Shell Wormholes in Einstein and Einstein–Gauss–Bonnet Theories of Gravity

Abstract: We review recent works on the possibility for eternal existence of thin-shell wormholes on Einstein and Einstein–Gauss–Bonnet gravity. We introduce thin-shell wormholes that are categorized into a class of traversable wormhole solutions. After that, we discuss stable thin-shell wormholes with negative-tension branes in Reissner–Nordström–(anti) de Sitter spacetimes in d-dimensional Einstein gravity. Imposing Z2 symmetry, we construct and classify traversable static thin-shell wormholes in spherical, planar and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 91 publications
(179 reference statements)
0
8
0
Order By: Relevance
“…We are going to finally assign the critical value μ c R = m/a c in (20) to μ R in (47), then take the leading order in the expansion of μ c R . For this, we now use two symbols, μ R and μ R :…”
Section: Effective Potential (2)mentioning
confidence: 99%
See 1 more Smart Citation
“…We are going to finally assign the critical value μ c R = m/a c in (20) to μ R in (47), then take the leading order in the expansion of μ c R . For this, we now use two symbols, μ R and μ R :…”
Section: Effective Potential (2)mentioning
confidence: 99%
“…• μ R : chemical potential on which the derivative with respect to μ R can act; finally the value m/a c is assigned, • μ R : just a symbol for the value m/a c R , on which the derivative with respect to μ R does not act. 6 In this section we have performed the expansion around μ R = 0 as in (47). However, if we expand around μ R = μ c R , we can obtain the following effective potential:…”
Section: Effective Potential (2)mentioning
confidence: 99%
“…Needless to say that many studies combine some or all of these trends. Nevertheless, it can be more or less conditionally observed that the first trend is represented by the papers [4,13,14,16], the second one by [5,7,11,15], and the third one by [6, 8-10, 12, 17]. Two of the papers are brief reviews [4,9].…”
mentioning
confidence: 99%
“…Nevertheless, it can be more or less conditionally observed that the first trend is represented by the papers [4,13,14,16], the second one by [5,7,11,15], and the third one by [6, 8-10, 12, 17]. Two of the papers are brief reviews [4,9]. Thus, Takafumi Kokubu and Tomohiro Harada [4] consider different physical aspects of thin-shell wormholes, both in GR and in Einstein-Gauss-Bonnet gravity, including spherical, planar and hyperbolic symmetries of space-time and the stability issues.…”
mentioning
confidence: 99%
See 1 more Smart Citation